Gender differences in chemical engineering students identified in understanding of rolling motion - Vidak, Andrej (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2020)
In this research papaer we presented the results of exploration of gender differences in conceptual understanding of rolling motion (velocities and work-energy principle). For this purpose, we have selected nine conceptual items and conducted experiment with 184 first year students at the Faculty of Chemical Engineering and Technology, University of Zagreb. Results show that male students significantly outperformed female students. We detected particularly large differences on items that tests knowledge of the rolling phenomena. Results of our research can help teachers to create lessons that are adapted to general student population.